Neuroottisuuden yhteys sosiaaliseen hyvinvointiin 10 vuoden seurannassa - Taulos, Anniina (2024)
Social well-being includes belonging to a community and its significance. In late adulthood, social well-being can be weakened by age-related losses and life changes, such as the deterioration of one’s own health and the death of loved ones. Neuroticism refers to a tendency towards anxiety, depression, mood swings and negative feelings. Neuroticism has long been recognized as one of the most important personality traits, as neuroticism has significant public health implications. The connection between neuroticism and social well-being and its domains (social integration, social coherence, social actualization, social contribution, and social acceptance) has not been investigated in European culture and not much in late adulthood. In this Master’s thesis, we find out whether neuroticism is associated with social well-being in a 10-year follow-up.